2021
DOI: 10.21896/jksmch.2021.25.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors on Intention to Receive Human Papillomavirus Vaccination in Mothers of Elementary School Girls: Focusing on the Mediating Effects of Self-efficacy

Abstract: Purpose: To provide basic data for the development of a nursing intervention program in order to improve intention to receive human papillomavirus (HPV) vaccination intention of mothers of elementary school girls by confirming the mediating effect of self-efficacy in the relationship between knowledge of HPV vaccine, attitude towards vaccination, subjective norm, and intention to receive vaccination.Methods: The subjects of this study are 171 mothers of elementary school students in grades 5–6 in Yangsan city.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Subthemes for facilitators are personal characteristics and environmental factors. The personal characteristics include attitude [ 12 , 24 , 35 , 36 ], subjective norms [ 12 , 24 , 28 , 36 ], awareness [ 38 ], self-efficacy [ 24 , 37 ], perceived benefits [ 25 , 31 , 34 ], perceived susceptibility [ 39 ], perceived barriers [ 31 , 39 ], and perceived behavior control [ 10 , 28 , 30 , 36 ], Some papers also mentioned a knowledge aspect to increase intention for HPV vaccination, namely education level [ 30 , 38 ] and high level of knowledge about vaccination [ 12 , 23 , 24 , 29 , 34 ]. Environmental factors were described by various descriptions such as family history of cervical cancer [ 38 ], clinician’s recommendation [ 29 , 30 , 39 ], mothers’ experience of pap-test, concerns about their daughters being high-risk subjects without HPV vaccination, mother’s experience with HPV vaccination [ 30 , 35 ], vaccination status of the health teachers [ 30 ] and their children [ 34 ], and the child’s teachers’ experience with pap-test [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subthemes for facilitators are personal characteristics and environmental factors. The personal characteristics include attitude [ 12 , 24 , 35 , 36 ], subjective norms [ 12 , 24 , 28 , 36 ], awareness [ 38 ], self-efficacy [ 24 , 37 ], perceived benefits [ 25 , 31 , 34 ], perceived susceptibility [ 39 ], perceived barriers [ 31 , 39 ], and perceived behavior control [ 10 , 28 , 30 , 36 ], Some papers also mentioned a knowledge aspect to increase intention for HPV vaccination, namely education level [ 30 , 38 ] and high level of knowledge about vaccination [ 12 , 23 , 24 , 29 , 34 ]. Environmental factors were described by various descriptions such as family history of cervical cancer [ 38 ], clinician’s recommendation [ 29 , 30 , 39 ], mothers’ experience of pap-test, concerns about their daughters being high-risk subjects without HPV vaccination, mother’s experience with HPV vaccination [ 30 , 35 ], vaccination status of the health teachers [ 30 ] and their children [ 34 ], and the child’s teachers’ experience with pap-test [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subthemes for the barriers to HPV vaccination included a lack of awareness and knowledge about HPV, concerns about side effects of the HPV vaccine [ 29 , 31 , 33 , 34 , 35 ], such as death, neurological disorders and thrombosis, mothers were reluctant to vaccinate their children, and the burden of HPV vaccine costs [ 32 , 33 ]. Some studies showed that adolescent mothers did not receive the HPV vaccine for their offspring because they did not know exactly what illness the HPV vaccine was related to [ 24 , 33 , 37 , 38 ] or did not feel the need to vaccinate [ 33 , 38 ]. Unvaccinated people around adolescents and lack of personal recommendations regarding HPV vaccination were also reasons not to vaccinate [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations